2019
DOI: 10.4049/jimmunol.1801247
|View full text |Cite
|
Sign up to set email alerts
|

Common Heritable Immunological Variations Revealed in Genetically Diverse Inbred Mouse Strains of the Collaborative Cross

Abstract: Variations in the proportion and number of specific immune cell types among healthy individuals are influenced by both heritable and nonheritable factors. Mouse models, subjected to fewer nonheritable factors than humans, allow the identification of genetic factors that shape the immune system. We characterized immunological trait variability in the Collaborative Cross (CC), a powerful genetic resource of recombinant inbred mouse strains derived from eight diverse founder strains. Of the 18 immunological trait… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 63 publications
2
33
0
Order By: Relevance
“…Furthermore, previous studies used a wide variety of different mouse strains, with different genetic backgrounds, for the mouse cancer models. Thus, the genetic variation among mouse strains could also contribute to the contradictory conclusions drawn for neutrophil interactions with tumor cells because immune phenotypes vary greatly among mice with different inbred genetic backgrounds 33 , 34 . In particular, mice with different levels of immune system integrity, such as immunocompetent versus immunodeficient mice, were variously utilized in cancer studies focusing on neutrophils 3 , 4 , 13 , 24 .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, previous studies used a wide variety of different mouse strains, with different genetic backgrounds, for the mouse cancer models. Thus, the genetic variation among mouse strains could also contribute to the contradictory conclusions drawn for neutrophil interactions with tumor cells because immune phenotypes vary greatly among mice with different inbred genetic backgrounds 33 , 34 . In particular, mice with different levels of immune system integrity, such as immunocompetent versus immunodeficient mice, were variously utilized in cancer studies focusing on neutrophils 3 , 4 , 13 , 24 .…”
Section: Introductionmentioning
confidence: 99%
“…Over the past several years, the CC has been used to model a wide range of biomedically relevant traits including: allergy (Orgel et al 2018), asthma (Donoghue et al 2017), behavior (Chesler 2014; Schoenrock et al 2018; Molenhuis et al 2018), bone development (Levy et al 2015), cancer (Dorman et al 2016; Reilly 2016), cellular immune phenotypes (Graham et al 2017), drug disposition (Nachshon et al 2016), exercise (McMullan et al 2018), fertility (Shorter et al 2017), glucose tolerance (Abu-Toamih Atamni et al 2017; Nashef et al 2017), infectious disease susceptibility (Durrant et al 2011; Ferris et al 2013; Rasmussen et al 2014; Gralinski et al 2015; Graham et al 2015; Graham et al 2016; Gralinski et al 2017; Green et al 2017; Abu Toamih Atamni et al . 2018; Zhang et al 2018; Collin et al 2019), motor performance and body weight (Mao et al 2015), spontaneous colitis (Rogala et al 2014), and toxicology (Cichocki et al 2017; Hartman et al 2017; Mosedale et al 2017; Venkatratnam et al 2017).…”
mentioning
confidence: 99%
“…Quantitation of total NK cells on days 1, 3 and 5 following IP inoculation of PBS or IL-15 are shown in Fig 1B. Following IL-15 treatment, NK cell numbers were dramatically higher on day 1 but progressively decreased over the next 4 days, although remaining significant (p = 0.057) relative to the PBS control throughout ( Fig 1B). Previous studies had shown extremely low numbers of NKT cells in CAST mice compared to classical inbred strains [42]. Indeed, of the eight Collaborative Cross strains, CAST mice had the lowest number of NKT cells (0.060% and 0.067% of total spleen lymphocytes for males and females, respectively).…”
Section: Il-15 Increases Nk and Cd8 + T Cell Numbers In Cast Micementioning
confidence: 88%